ASSIMILATIVE FEATURES OF BORROWING IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES - Yakubova Noira Isxakovna (American Journals, 2023)
In the article at least 3 words - adaptive, assimilation, and integration terms that penetrated the Uzbek language through Russian and English, and words of adaptation, mastery, strengthening (fixation, refreshing, strengthening) in accordance with the norms of the accepted language and the phonetic, grammatical specifics of the mastered units regarding the formation of lexical semantics.
Keywords: borrowing, terminology, languages, assimilation features, grammatical, phonetic, semantic, adaptation.